2013
DOI: 10.1111/nph.12611
|View full text |Cite
|
Sign up to set email alerts
|

High‐density genome‐wide association mapping implicates an F‐box encoding gene in Medicago truncatula resistance to Aphanomyces euteiches

Abstract: SummaryThe use of quantitative disease resistance (QDR) is a promising strategy for promoting durable resistance to plant pathogens, but genes involved in QDR are largely unknown. To identify genetic components and accelerate improvement of QDR in legumes to the root pathogen Aphanomyces euteiches, we took advantage of both the recently generated massive genomic data for Medicago truncatula and natural variation of this model legume.A high-density (%5.1 million single nucleotide polymorphisms (SNPs)) genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 82 publications
(123 reference statements)
5
115
0
Order By: Relevance
“…Examples of where LD mapping has been applied for identification of both novel and previously characterized genes responsible for agronomic traits include genome‐wide association studies (GWAS) in model legume Medicago truncatula (Stanton‐Geddes et al, ), common bean (Kamfwa, Cichy, & Kelly, ; Moghaddam et al, ), and soybean (Contreras‐Soto et al, ; Zhou et al, ). GWAS has also proven to be successful in identifying candidate genes for ascochyta blight resistance (Li et al, ) and heat and drought tolerant loci in chickpea (Thudi, Upadhyaya, et al, ), and Aphanomyces euteiches resistance in Medicago truncatula (Bonhomme et al, ). Applying GWAS in a population comprising 292 pigeonpea accessions using data over several years enabled identification of association between candidate genes and traits, including 100‐seed weight, days to 50% flowering, and plant height (Varshney et al, ).…”
Section: Finding Adaptive Genes and Adaptive Traitsmentioning
confidence: 99%
“…Examples of where LD mapping has been applied for identification of both novel and previously characterized genes responsible for agronomic traits include genome‐wide association studies (GWAS) in model legume Medicago truncatula (Stanton‐Geddes et al, ), common bean (Kamfwa, Cichy, & Kelly, ; Moghaddam et al, ), and soybean (Contreras‐Soto et al, ; Zhou et al, ). GWAS has also proven to be successful in identifying candidate genes for ascochyta blight resistance (Li et al, ) and heat and drought tolerant loci in chickpea (Thudi, Upadhyaya, et al, ), and Aphanomyces euteiches resistance in Medicago truncatula (Bonhomme et al, ). Applying GWAS in a population comprising 292 pigeonpea accessions using data over several years enabled identification of association between candidate genes and traits, including 100‐seed weight, days to 50% flowering, and plant height (Varshney et al, ).…”
Section: Finding Adaptive Genes and Adaptive Traitsmentioning
confidence: 99%
“…These results have been corroborated by genetic studies. A major locus associated with resistance to A. euteiches , namely AER1 , has been identified (Pilet‐Nayel et al ., ) and confirmed by a genome‐wide association study, which identified two major independent loci on top of chromosome 3, one of which co‐localized with prAe1 (formerly named AER1) (Bonhomme et al ., ). The functional role of the prAe1 locus has been investigated recently (Badis et al ., ) using two near‐isogenic lines, NR and NS, partially resistant and susceptible, respectively, differing in the allelic state of prAe1.…”
Section: Introductionmentioning
confidence: 97%
“…(2011) as a potential contributor to climate-specific survival in A. thaliana, and an M. truncatula homolog of the A. thaliana CPR30 has been shown to confer resistance to the oomycete Aphanomyces euteiches (Bonhomme et al 2014). Bonhomme et al also speculated that this M. truncatula F-box gene may play a direct role in response to abiotic stress.…”
Section: Functional Roles Of Candidatesmentioning
confidence: 99%